Effect of solid to liquid ratio on the mechanical and physical properties of fly ash geopolymer without sodium silicate - Abdul Rahim, R.H. (Trans Tech Publications Ltd, 2014)
Geopolymer is produced from the alkali activation of materials rich in Si and Al with addition of silicate solution in order to improve the mechanical property. Limited research has been done with the absence of silicate solution in the geopolymerization process by varying solid/liquid ratio and on how it works for that condition on mechanical and physical properties. This paper presents an investigation on the mechanical and physical properties of fly ash based geopolymer by varying solid to liquid ratio using sodium hydroxide as the only activator. In addition, the strength development also been investigated. The samples were prepared using 50mm x 50mm x 50mm mould and cured at an elevated temperature (60oC). It can be observed that the optimum compressive strength and density were obtained at solid/ liquid ratio of 4. In addition, the compressive strength of fly ash based geopolymer for all the solid to liquid ratio increased until 14 days and started to decrease later. Â© 2014 Trans Tech Publications, Switzerland.